1991
DOI: 10.1088/0951-7715/4/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Slowly pulsating separatrices sweep homoclinic tangles where islands must be small: an extension of classical adiabatic theory

Abstract: The universal description of orbits in the domain swept by a slowly varying separatrix is provided through a symplectic map derived by means of an extension of classical adiabatic theory. This map connects action-angle-like variables of an orbit when far from the instantaneous separatrix to time-energy variables at a reference point of the orbit very close to the corresponding separatrix. map with WKB theory to obtain a description of the structure underlying chaos: the homoclinic tangle related to the hyperbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 21 publications
4
89
0
Order By: Relevance
“…Conversely, if the surface of section in (Υ, υ) plane reveals an area-filling manifold, conservation of J is broken as the orbit repeatedly encounters a separatrix in the (Ξ, ξ) plane (Henrard 1982a;Morbidelli 2002). Indeed the situation is quite analogous to the well-studied problem of a modulated pendulum (Elskens & Escande 1991;Bruhwiler & Cary 1989). A surface of section of the (Correia et al 2009) orbital solution is shown as a thick purple line in Fig.…”
Section: Adiabatic Evolutionmentioning
confidence: 91%
“…Conversely, if the surface of section in (Υ, υ) plane reveals an area-filling manifold, conservation of J is broken as the orbit repeatedly encounters a separatrix in the (Ξ, ξ) plane (Henrard 1982a;Morbidelli 2002). Indeed the situation is quite analogous to the well-studied problem of a modulated pendulum (Elskens & Escande 1991;Bruhwiler & Cary 1989). A surface of section of the (Correia et al 2009) orbital solution is shown as a thick purple line in Fig.…”
Section: Adiabatic Evolutionmentioning
confidence: 91%
“…Statistical independence follows from the divergence of phases along trajectories. For separatrix crossings consecutive crossings for some initial conditions are statistically dependent (Cary and Skodje, 1989) and islands of stability, albeit being of a small measure, do exist (Elskens and Escande, 1991;Neishtadt et al, 1997) inside large chaotic see. Consecutive resonance crossings should be treated as independent as shows the following reasoning from (Neishtadt, 1999).…”
Section: The Long-time Behaviour Of the Particlesmentioning
confidence: 99%
“…when τ discr ≫ τ spread , numerical calculations revealed [30] that after a time τ s ∼ τ spread , ⟨∆v 2 (t)⟩ grows with a slope in between the quasilinear one and 2.3 times this value 42 (in the range 40 In the opposite limit when τ spread /τac is small, the time evolution of the waves is slow with respect to the trapping motion in the instantaneous wave potential. Then chaotic dynamics may be described in an adiabatic way with the picture of a slowly pulsating separatrix [46,47] (see also section 5.5 of [48] and 14.5.2 of [54]). In this limit, for the case of the motion in two waves, the resonance overlap defined hereafter is large.…”
Section: Diffusion In a Given Spectrum Of Wavesmentioning
confidence: 99%